Innovation, industrial and trade policies for technological sovereignty - Jürgen Janger (FIW - Research Centre International Economics, 2024)
Interrupted supply chains in the wake of COVID-19 and Russia's attack on Ukraine have highlighted the geopolitical risks of sourcing critical raw materials and products from a small number of authoritarian countries. The EU has initiated a flurry of activities to reduce unilateral dependencies, witnessed by trade, innovation and industrial policy instruments, such as the IPCEIs, the Chips Act and new anti-subsidy measures. This policy brief focuses on fostering technological sovereignty to insure against risks from international trade specifically in critical general purpose technologies. Bundles of innovation, industrial and trade policies enter three consistent policy mixes according to the distance to the technological frontier: for emerging technologies, the frontier policy mix emphasises an improvement in general framework conditions such as a more integrated European capital market. Technologies which lag behind the frontier benefit from coordinated support within the catch-up policy mix, while technologies at risk of losing their position at the frontier fall within the remit of the defensive policy mix. – – Unterbrochene Lieferketten im Zuge von COVID-19 und Russlands Angriff auf die Ukraine haben die geopolitischen Risiken der Beschaffung kritischer Rohstoffe und Produkte aus einer kleinen Zahl autoritärer Länder deutlich gemacht. Die EU hat eine Reihe von Aktivitäten eingeleitet, um einseitige Abhängigkeiten zu verringern, was durch handels-, innovations- und industriepolitische Instrumente wie die IPCEI, den Chips Act und neue Antisubventionsmaßnahmen belegt wird. Dieser Policy Brief konzentriert sich auf die Förderung der technologischen Souveränität zur Absicherung gegen Risiken aus dem internationalen Handel speziell mit kritischen Allzwecktechnologien. Bündel von innovations-, industrie- und handelspolitischen Maßnahmen lassen sich je nach Abstand zur technologischen Grenze in drei konsistente Policy-Mixes einteilen: Bei aufstrebenden Technologien liegt der Schwerpunkt des Policy-Mix für die Grenze auf einer Verbesserung der allgemeinen Rahmenbedingungen, wie etwa einem stärker integrierten europäischen Kapitalmarkt. Technologien, die hinter der Grenze zurückbleiben, profitieren von einer koordinierten Unterstützung im Rahmen des "catch-up policy mix", während Technologien, die Gefahr laufen, ihre Position an der Grenze zu verlieren, in den Bereich des "defensiven policy mix" fallen.
Keywords: 330